Al-Muwathanah Concept for non Muslims in Islamic majority Countries Siyasah Fikih Perspective - Lukman Arake (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2019)
The Islamic priests do not use the word of minority (akalliyah) in the literature of classical Islamic jurisprudence when they talk about the existence of non-Muslims in Islamic countries, but they use the term of ahluzzimmah. Their reason not to use that term is because Islam itself does not distinguish the rights and obligations between Muslims or non-Muslims who live in a country, except those closely related to religious issues. This was caused by the actualization concept from one of religion rule